Sexual Harassment on Males in Public Transport - Thennakoon, M. S. B. W. T. M. E. M. (University of Jaffna, 2018)
Although sexual harassments of women in public transport have been studied over the years which were considered as an issue related to power, men are also targets of sexual harassments in public transport although there are limited studies which have focused on their experiences. To address this gap the researcher has attempted to answer the question “How do men get harassed in Public transportation? And how do men react in these instances”, through an exploratory study. The main objectives of this study were to understand the nature of sexual harassment men face in public transportation and to identify the reactions of men to sexual harassments they faced in public transportation. Researcher has used qualitative method in this study conducting in-depth semi structured interviews of 15 male respondents of age between 20 to 25 to explore and explain their experiences and responses to sexual harassments in public transport. In this exploratory study the researcher discovered that the men are also victims of sexual harassment in public transport although the general perception of sexual harassment in public transport always refers to women. Furthermore harassers of sexual harassments on men were mainly males, as well as some female, gay, bisexual and transgender individuals. The men appear to have faced physical, verbal and implied sexual harassments. Men’s reactions to the sexual harassments were sometimes assertive and sometimes non-assertive where theyhave received less assistance of others when they have faced sexual harassments in public transport.
Keywords: Harassers; Men; Public transport; Sexual harassments